Propuesta de enseñanza para la construcción de la fórmula de volumen prisma rectangular recto - García, Alejandro; Marmolejo, Gustavo A. (Revista SIGMA, 2018)
Abstract The teaching of the measure privileges the premature use of formulas whose inclusion makes no sense and meaning for students. In consecuence, the reﬂection on processes of construction of formulas that emphasize in the link between the reached algorithm and the aforementioned concept are issues to consider. In this sense, the article exposes a teaching proposal that elicits the construction of the formula to calculate the volume of a straight rectangular prism. For the design of the teaching proposal we consider the visual perspective of [3, 4, 5]. In particular, diﬀerent types of visual operations, dimensional changes and control variables were assumed as design variables. The visualization links the magnitude volume with the qualitative characteristics that, in a solid determine his study. Finally, the article sets out guidelines for the implementation of the proposal. Resumen La enseñanza de la medida privilegia el uso prematuro de fórmulas cuya inclusión carece de sentido y signiﬁcado para los estudiantes. Por tanto, la reﬂexión sobre procesos de construcción de fórmulas que enfaticen en el vínculo entre el algoritmo alcanzado y el concepto aludido, deben ser cuestiones a considerar. En este sentido, el artículo, expone una propuesta de enseñanza que suscita la construcción de la fórmula para calcular el volumen de un prisma rectangular recto. Para su diseño se consideró la perspectiva visual de [3, 4, 5], en particular, como variables de diseño, se asumieron diferentes tipos operaciones visuales, cambios dimensionales y variables de control. La visualización vincula la magnitud volumen a las características cualitativas que, en un sólido determinan su estudio. Finalmente, se exponen pautas para la aplicación de la propuesta.